A situational analysis of regional investments, policies, legislation and advocacy efforts on food-based approaches to combating micronutrient deficiency in Sub-Saharan Africa: focus on biofortification - International Potato Center (International Potato Center, 2017)
This situation analysis report provides a snapshot of the regional and subregional policies and frameworks that support biofortification and the organizations implementing various nutritionsensitive initiatives. The report identifies some ongoing initiatives that are relevant to the Building Nutritious Food Baskets (BNFB) Project mandate and that can be aligned to its activities to facilitate its starting up and scaling up. The report recommends the key actions necessary to facilitate increased investment in and scaling up of biofortified crops in sub-Saharan Africa. It also provides guidance on the broad strategic areas that could form the focus in the development of a regional advocacy strategy for the BNFB Project, and serve as the basis of a plan of work for biofortification advocacy champions for stimulating sustainable investments in the production and consumption of biofortified crops.